The Effect of Economic Performance and Expansion of Access on Income Distribution in Regency/City in Indonesia - Ernawati Ernawati; Wali Aya Rumbia; Tajuddin Tajuddin (Universitas Ahmad Dahlan, 2021)
Quality economic development is indicated by inclusive economic development, where an increase in economic performance is accompanied by an increase in welfare such as income distribution. This study aims to determine the effect of economic performance and expansion of access to income distribution in Indonesia. The study used secondary data from the Indonesian Inclusive Development Index published by the National Development Planning Agency for 464 districts/cities in 2019. Data analysis using multiple linear regression. The results showed a positive correlation between economic performance, expansion of access to public services and income distribution in Indonesia. However, expansion of access does not significantly affect income distribution, while economic performance has a significant effect. On the other hand, the condition of the income distribution in the previous period had a significant effect on the achievement of the income distribution for the next period. Improved economic performance and improved income distribution in the previous period will increase Indonesia's income distribution.